Trends and Applications of Body Donation Program in Mahakaushal Region - Natwar Lal Agrawal; Mayura Setiya; Kranti Kumar Gour (Wolters Kluwer Medknow Publications, 2020)
Introduction: Body donation or body endowment is defined as a desired program of donating one's body after death for progress of medical research and as a segment of medical education. In recent times, attitude, knowledge, and awareness have played a pivotal role in changing the trends of body donation. Methods: Data pertaining to 64 voluntary donated cadavers were studied over a period of 13 years in our anatomy department. Age, sex, and other data were noted and analyzed statistically. Results: An increasing trend in the profile of body donation was observed between 2015 and 2017. More male cadavers (60.9%) were donated than females (39.1%). The youngest cadaver was male (17 years), whereas the oldest cadaver was female (96 years). Cadavers were generally elderly, with an average age of 72.9 years. Conclusion: The present study is a forward step in field of database study of trends of increasing body donation which forms a key tool for anatomists and provides students and surgeons with exceptional chance to study the structure of human body. The present-day trend of body donation in our institute is sufficient to meet the demands of cadavers as per Medical Council of India (MCI) rules.